Evaluation of Individual Competitiveness and the Relationship Between Competitiveness and Yield in Maize. Issue 5 (1st September 2015) - Zhai, Lichao; Xie, Ruizhi; Ma, Daling; Liu, Guangzhou; Wang, Pu; Li, Shaokun
ABSTRACT: Competition plays an important role in ecology and is also a common phenomenon in agricultural production. The objectives of this study were to (i) investigate the yield variability of maize ( Zea mays L.) cultivars and populations in mixtures, (ii) evaluate the competitiveness of maize cultivars, and (iii) evaluate the relationship between competitiveness and grain yield. A 2‐yr (2012–2013) field experiment was conducted using the de Wit replacement series desSign. Two maize cultivars, Yedan13 (YD13) and Zhongdan909 (ZD909), were grown in seven different YD13/ZD909 combinations (0:6, 1:5, 1:2, 1:1, 2:1, 5:1, and 6:0) with a plant density of 67, 500 plants ha −1 . Yield variability was observed on individual plant and population levels in different mixtures of both maize cultivars. Grain and dry matter yield per plant for each cultivar and population level decreased as the proportion of YD13 increased, and grain yield per plant was always lowest for YD13. However, the relative yield (RY) of YD13 was higher than that of ZD909 in all mixtures. Analyses of competition indices (RY, aggressivity, and relative severity of competition) indicated that YD13 was more competitive than ZD909. These results demonstrated that maize cultivars differ in their competitiveness. In addition, enhanced competitive pressure was accompanied by a reduction in yield performance. These results suggest a negative relationship between maize competitiveness and grain yield.